Perceived Teacher Support and Communication in Strategizing Possible Selves - Mireles-Rios, Rebeca; Roshandel, Shadi (Frontiers in Education, 2020)
There is limited insight into how perceived teacher support and communication may be related to the development of adolescents’ strategies to achieve a hoped for and expected possible selves while avoiding their feared possible selves. This study explores the relationship between adolescents’ perceptions of their teachers’ support and communication and their possible selves. A total of 85 adolescents (Mage = 15.5 years) participated (45% White and 55% Latino). A mixed-method strategy was used which included survey data and semi-structured interviews. Findings indicate that perceived teacher support is associated with adolescents’ development of concrete strategies. Our study found that when students perceived their teachers communicated with them about the future, the more concrete strategies they had to address their range of possible selves. This study begins to uncover the role teachers play in supporting and shaping how all adolescents can construct an action plan that will lead to the desired outcomes.